Mitomycin-Induced Pulmonary Veno-Occlusive Disease: Evidence From Human Disease and Animal Models. Issue 9 (1st September 2015) - Perros, Frédéric; Günther, Sven; Ranchoux, Benoit; Godinas, Laurent; Antigny, Fabrice; Chaumais, Marie-Camille; Dorfmüller, Peter; Hautefort, Aurélie; Raymond, Nicolas; Savale, Laurent; Jaïs, Xavier; Girerd, Barbara; et al.
Abstract : Background—: Pulmonary veno-occlusive disease (PVOD) is an uncommon form of pulmonary hypertension characterized by the obstruction of small pulmonary veins and a dismal prognosis. PVOD may be sporadic or heritable because of biallelic mutations of the EIF2AK4 gene coding for GCN2. Isolated case reports suggest that chemotherapy may be a risk factor for PVOD. Methods and Results—: We reported on the clinical, functional, and hemodynamic characteristics and outcomes of 7 cases of PVOD induced by mitomycin-C (MMC) therapy from the French Pulmonary Hypertension Registry. All patients displayed squamous anal cancer and were treated with MMC alone or MMC plus 5-fluoruracil. The estimated annual incidence of PVOD in the French population that have anal cancer is 3.9 of 1000 patients, which is much higher than the incidence of PVOD in the general population (0.5/million per year). In rats, intraperitoneal administration of MMC induced PVOD, as demonstrated by pulmonary hypertension at right-heart catheterization at days 21 to 35 and major remodeling of small pulmonary veins associated with foci of intense microvascular endothelial-cell proliferation of the capillary bed. In rats, MMC administration was associated with dose-dependent depletion of pulmonary GCN2 content and decreased smad1/5/8 signaling. Amifostine prevented the development of MMC-induced PVOD in rats. Conclusions—: MMC therapy is a potent inducer of PVOD in humans and rats. Amifostine prevents MMC-induced PVOD in rats and should be tested as a preventive therapy for MMC-induced PVOD in humans. MMC-induced PVOD in rats represents a unique model to test novel therapies in this devastating orphan disease. Abstract : Supplemental Digital Content is available in the text.